Dosimetry and Toxicity Studies of the Novel Sulfonamide Derivative of Sulforhodamine 101([18F]SRF101) at a Preclinical Level - Kreimerman, Ingrid (2019)
Abstract: Background: The SR101 N-(3-[18F]Fluoropropyl) sulfonamide ([18F]SRF101) is a Sul forhodamine 101 derivative that was previously synthesised by our group. The fluorescent dye SR101 has been reported as a marker of astroglia in the neocortex of rodents in vivo. Objective: The aim of this study was to perform a toxicological evaluation of [18F]SRF101 and to esti mate human radiation dosimetry based on preclinical studies. Methods: Radiation dosimetry studies were conducted based on biokinetic data obtained from a mouse model. A single-dose toxicity study was carried out. The toxicological limit chosen was <100 µg, and allometric scaling with a safety factor of 100 for unlabelled SRF101 was selected. Results: The absorbed and effective dose estimated using OLINDA/EXM V2.0 for male and female dosimetric models presented the same tendency. The highest total absorbed dose values were for dif ferent sections of the intestines. The mean effective dose was 4.03 x10-3 mSv/MBq and 5.08 x10-3 mSv/MBq for the male and female dosimetric models, respectively, using tissue-weighting factors from ICRP-89. The toxicity study detected no changes in the organ or whole-body weight, food consumption, haema tologic or clinical chemistry parameters. Moreover, lesions or abnormalities were not found during the histopathological examination. Conclusion: The toxicological evaluation of SRF101 verified the biosafety of the radiotracer for hu man administration. The dosimetry calculations revealed that the radiation-associated risk of [ 18F]SRF101 would be of the same order as other 18F radiopharmaceuticals used in clinical applica tions. These study findings confirm that the novel radiotracer would be safe for use in human PET imaging.